Survey of Exotic Species in Conservation Units: The Case of the State of Rio de Janeiro (Research, Society and Development, 2019)
The growing increase in the human population has been causing biodiversity to be reduced. Processes such as habitat loss and fragmentation, excessive exploitation of plant and animal species and the introduction of exotic species contribute to this loss. In this context, this study aimed to carry out a survey on the occurrence of exotic species of fauna and flora in the federal and state conservation units of the state of Rio de Janeiro.  Initially, there was a consultation of the management plans of the units through the sites of the Chico Mendes Institute for Biodiversity Conservation (ICMBio) and the State Institute of Environment (INEA). In order to systate the analyzed data, four categories were created referring to the management plans, Category 1: without management plan; Category 2: Without management plan, but which have a decree published in the Official Gazette of the Union, which establishes the elaboration of official document; Category 3: With management plan, but no type of exotic species is cited; Category 4: With management plan, where exotic species are cited. Among the animal species, the most common to these UCs was the star-white-tufed Tamarin (Callithrix jacchus Linnaeus, 1758), found in 10 UCs and among the plant species, the most common was the Jaqueira (Artocarpus heterophyllus Linnaeus, 1753), found in 11 UCs. This study provided information and a report on the distribution pattern, in the federal and state UCs of the state of Rio de Janeiro, of species that has the ability to cause imbalance in different ecosystems.